Immediate reporting of chest X-rays referred from general practice by reporting radiographers: a single centre feasibility study. Issue 5 (May 2018) - Woznitza, N.; Piper, K.; Rowe, S.; Bhowmik, A.
Abstract : Aim: To investigate the feasibility of radiographer-led immediate reporting of chest radiographs (CXRs) referred from general practice. Materials and methods: This 4-month feasibility study (November 2016 to March 2017) was carried out in a single radiology department at an acute general hospital. Comparison was made between CXRs that received an immediate and routine report to determine the number of lung cancers diagnosed, time to diagnosis of lung cancer, time to computed tomography (CT), and number of urgent referrals to respiratory medicine. Results: Forty of 186 sessions (22%) were covered by radiographer immediate reporting. Of the 1, 687 CXRs referred from general practice, 558 (33.1%) received an immediate report (radiographer or radiologist). Twenty-two (of 36) CT examinations performed were following an abnormal CXR with an immediate report (mean 0.8 scans/week). Time from CXR to CT was shorter in the immediate report group (n=22 mean 0.9 days SD=2.3) compared to routine reporting (n=14; mean 6.5 SD=3.2; F=27.883, p< 0.0001). Time to multidisciplinary team (MDT) discussion was shorter in the immediate reporting group (mean 4.1 SD=2.9) compared to routine reporting (mean 10.6; SD=4.5; F=11.59, p< 0.0001). No apparent difference was found for time to discussion at treatment MDT. Conclusion: It is feasible to introduce a radiographer-led immediate CXR reporting service. Patients can be taken off the lung cancer pathway sooner with the introduction of radiographer immediate reporting of CXRs and this may improve outcomes for patients. A definitive study assessing outcomes is required to determine whether this will have an impact mortality and morbidity for patients. Highlights: Early lung cancer diagnosis is often limited by insufficient radiology capacity. It is feasible to introduce immediate reporting of chest X-rays from general practice by radiographers. Time to diagnosis of lung cancer can be significantly shortened with immediate chest X-ray reporting.